Analisis Aktivitas Ekonomi Masyarakat Dan Nilai Ekonomi Daerah Aliran Sungai Saat Terdampak Pandemi COVID-19 Di Kelurahan Panamas Kecamatan Selat Kabupaten - Rinto Alexandro; Windy Utami Putri; Merisa Oktaria (FKIP, Universitas Palangka Raya, 2021)
This study reveals about phenomena in society using descriptive methods. Problems in society will be studied and illustrated. Through this descriptive method, the researcher wants to describe the phenomenon about the research object so that he will find scientific truths about the phenomena that occur in the research object.